A comparison of two phonological screening tools for French-speaking children - Bérubé, Daniel; Macleod, Andrea A. N. (International Journal of Speech-Language Pathology, 2022)
Purpose: To examine two screening tools for phonological production, the Evaluation Sommaire de la Phonologie chez l’enfant d’âge préscolaire (ESPP) and the Test de Phonologie du Français Canadien-Dépistage (TPFC-D), developed according to differing theoretical perspectives. The TPFC-D, designed according to nonlinear phonology, includes more words and contains a greater variety of segments across word structure as compared to the ESPP, which was guided by a linear phonological framework. The greater response rate to test items, time of administration, and phonological complexity were expected on the TPFC-D. Method: Each screening tool was administered to 14 4-year-old French-speaking children living in Central Canada. Paired samples t-tests compared children’s responses on the two tasks with regards to (a) response rate and time of administration, (b) an overall percentage of consonants correct (PCC) and percentage of vowel correct (PVC), and (c) complexity of productions (i.e. PCC and PVC in relation to word structure, Word Shape Match, Whole Word Match, Phonological Mean Length of Utterance (pMLU) and Proportion of Whole-Word Proximity). Result: Item response rates were higher for the TPFC-D whereas time of administration, PCC and PVC were similar for both the ESPP and TPFC-D. Complexity measures showed a higher proportion of deletions in clusters and higher pMLUs on the TPFC-D compared to the ESPP. Conclusion: Both screening measures are appropriate for speech-language pathologists who want to assess quickly pre-school-aged children. Since the TPFC-D is phonologically more complex, it is recommended for clinicians needing to screen children who likely present with multiple speech sound errors across their phonological system.

The gendered migrant experience: a study of family language policy (FLP) amongst mothers and daughters in the Somali community, Bristol - Selleck, Charlotte (Current Issues in Language Planning, 2023)

Taux de pauvreté au sein de la population bilingue du Québec, du Nouveau-Brunswick et de l’Ontario, 2021 - Statistique Canada (2021)